2020
DOI: 10.34172/joddd.2020.021
|View full text |Cite
|
Sign up to set email alerts
|

Association of MAPK4 and SOX1-OT gene polymorphisms with cleftlip palate in multiplex families: A genetic study

Abstract: Background. Cleft lip and palate (CLP) is a common congenital anomaly. Many genes, like MAPK4 andSOX-1OT, are associated with its etiology in different populations. High-risk markers on these genesreported in other populations were not studied in our population. Hence, the study aimed to determinethe association of MAPK4 and SOX-1OT polymorphisms in CLP in multiplex families. Methods. Based on inclusion and exclusion criteria, we selected 20 multiplex CLP families for thiscase‒control study, in which the aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…The variations in the results could be attributed to geographical differences, epigenetic factors, gene–environment interaction, etc. 31 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The variations in the results could be attributed to geographical differences, epigenetic factors, gene–environment interaction, etc. 31 …”
Section: Discussionmentioning
confidence: 99%
“…The variations in the results could be attributed to geographical differences, epigenetic factors, gene-environment interaction, etc. 31 In the present study, 40 case-parent trios were included. The SNPs rs9439714, rs1339062, rs6695765, rs742071, and rs618941 of PAX7 were genotyped using the Agena Bio MassARRAY platform.…”
Section: Discussionmentioning
confidence: 99%
“…The family studies for the Indian population reported that several genes such as CRISPLD2, RUNX2, SOX1-OT, MAPK4, CTIF, MYO5B, SMAD7, LOXHD1, and SKA1 are not associated with NSCLP in Indian multiplex families. [15][16][17] However, there are no reported case-parent trio studies of the PAX7 gene in the Indian population. Case-parent trio design studies are generally used in genetics, in which the affected children and their parents (father and mother) are genotyped.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, 30% of clefts are syndromic and are associated with a few other developmental anomalies. 25 …”
Section: Epidemiologymentioning
confidence: 99%
“…In contrast, 30% of clefts are syndromic and are associated with a few other developmental anomalies. 25 The frequency of occurrence of OFC differs with regard to gender and side of clefting. Cleft lip is more common in males at a 2:1 male to female ratio, whereas a cleft palate is more common in females.…”
Section: Introductionmentioning
confidence: 99%